PREGNANCY IN ELDERLY - Bendezú Martínez, Guido (2015)
Objective: To determine pregnancy and newborn outcome in women over 35 years old. Design: Retrospective, transversal, case-control study, from January 1 through December 31, 1999. Setting: Obstetrical Service, Ica EsSalud "Félix Torrealva Gutiérrez" Hospital. Material and Methods: Two hundred and seventy-six pregnant women aged 35 or over were compared with a similar number of 20 to 34 year-old pregnant women. Results: During 1999 1343 deliveries were attended, 267 belonging to 35 year-old or older women (19,9%). Median age was 37,8, and 27,7 in the control group. Median length of gestation was 38,3 weeks, versus 39,5 weeks in the control group. Cesarean section was performed in 29,6% of deliveries, 19,1% in the control group. Previous cesarean section was the first indication in both groups, 6,7% and 5,9%. Breech presentation occurred in 2,9%. Toxemia (6,7%) and premature rupture of membranes (PROM) (16,5%) were more frequent in older pregnant women. Macrosomic and large for gestational age newborns represented 8,9% and 11,9%, respectively, as well as obstetrical trauma (4,5%) and post partum hemorrhage (10,1%). Conclusions: In pregnant women 35 year-old or older we found higher incidence of multiple pregnancy, macrosomic and large for gestational age, low-weight newborns, cesarean section, toxemia, PROM, post partum hemorrhage.